Impact of Background Traffic on Speech Quality in VoWLAN - Peter Počta; Peter Kortiš; Martin Vaculík (Advances in Multimedia)
This paper describes measurements of the impact of background traffic on speech quality in an environment of WLANs (IEEE 802.11). The simulated background traffic consists of three types of current traffics in telecommunication networks such as data transfer service, multimedia streaming service, and Web service. The background traffic was generated by means of the accomplished Distributed Internet Traffic Generator (D-ITG). The impact of these types of traffic and traffic load on speech quality using the test sequence and speech sequences is the aim of this paper. The assessment of speech quality is carried out by means of the accomplished Perceptual Evaluation of Speech Quality (PESQ) algorithm. The proposal of a new method for improved detection of the critical conditions in wireless telecommunication networks from the speech quality point of view is presented in this paper. Conclusion implies the next application of the method of improved detection of critical conditions for the purpose of algorithms for link adaptation from the speech quality point of view in an environment of WLANs. The primary goal of these algorithms is improving speech quality in the VoWLAN connections, which are established in the competent link.